2016
DOI: 10.1007/978-3-319-43696-8_14
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerabilities of Government Websites in a Developing Country – the Case of Burkina Faso

Abstract: Abstract. Slowly, but consistently, the digital gap between developing and developed countries is being closed. Everyday, there are initiatives towards relying on ICT to simplify the interaction between citizens and their governments in developing countries. E-government is thus becoming a reality: in Burkina Faso, all government bodies are taking part in this movement with web portals dedicated to serving the public. Unfortunately, in this rush to promote government actions within this trend of digitization, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Previous studies were not able to solve this apparent anomaly by assessing the quality of e-government websites. (Zhao et al, 2010;Bissyandé et al, 2016;Ali and Zamri Murah, 2018). However, in the study conducted by Thompson et al (2020), the quality of e-government websites was studied in terms of cybersecurity across two countries (Australia and Thailand).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies were not able to solve this apparent anomaly by assessing the quality of e-government websites. (Zhao et al, 2010;Bissyandé et al, 2016;Ali and Zamri Murah, 2018). However, in the study conducted by Thompson et al (2020), the quality of e-government websites was studied in terms of cybersecurity across two countries (Australia and Thailand).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Zhao et al (2010) assessed 50 US states and found several security flaws, which would expose the IP addresses of the websites. Similarly, other countries were also evaluated, namely, Nigeria (Awoleye et al, 2012;Awoleye et al, 2014), Kyrgyz Republic (Ismailova, 2017), Jordan (Alsmadi and Shanab, 2016), Burkina Faso (Bissyandé et al, 2016) and Libya (Ali and Zamri Murah, 2018). Results from these studies recommend that policies should be in place to assist e-government services to improve authenticity, thereby gaining public and business trust.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%